Penguatan Literasi Qur’ani dan Akhlak Islami Anak Melalui Kegiatan Taman Pendidikan Al-Qur’an - Zulfa Hafidzah (Edujavare Publishing, 2025)
This community service activity aims to analyze the effectiveness of Quranic Education Park (TPQ) at Al-Ma'ruf Mosque in strengthening children's Quranic literacy and Islamic character as a response to the challenges of Islamic education in the modern era facing rapid technological development and globalization. The method used is a participatory approach involving TPQ managers, teachers (ustadzah), parents, and students through stages of initial observation, program design, activity implementation, and evaluation that includes Quranic reading learning (tahsin, tajwid, and memorization), Islamic character habituation, tilawah classes, muroja'ah, exemplary stories, worship practice, and Islamic character habituation in daily life. The activity results show positive impacts in the form of improved Quranic reading abilities with children reading more fluently, understanding the basics of tajwid, and increasing in surah memorization; strengthening Islamic character habits where children are accustomed to giving greetings, maintaining cleanliness, praying before and after learning, and showing respect to teachers; increased learning enthusiasm with stable children's attendance and high involvement in activities; as well as full support from parents and mosque administrators. This community service activity successfully demonstrates that Quranic learning combined with Islamic character cultivation through daily habituation can improve the ability to read, understand, and practice the Quran, so that this educational model can serve as a reference for other TPQs in facing globalization challenges while maintaining a strong Islamic identity.